The International Family Study of Nonsyndromic Orofacial Clefts: Design and Methods. (April 2022) - Auslander, Allyn; McKean-Cowdin, Roberta; Feigelson, Devin; Brindopke, Frederick; DiBona, Melissa; Magee, Kathy; Arakaki, Lili; Kapoor, Rijuta; Ly, Stephanie; Conti, David V.; Rakotoarison, Sylvia; Mahmoudi, Fouzia; et al.
Background: The majority of research to understand the risk factors of nonsyndromic orofacial clefts (NSOFCs) has been conducted in high-income populations. Although patients with NSOFCs in low- and middle-income countries (LMICs) are at the highest risk of not receiving care, global health infrastructure allows innovative partnerships to explore the etiologic mechanisms of cleft and targets for prevention unique to these populations. Methods: The International Family Study (IFS) is an ongoing case–control study with supplemental parental trio data designed to examine genetic, environmental, lifestyle, and sociodemographic risk factors for NSOFCs in 8 LMICs (through August 2020). Interview and biological samples are collected for each family. The interview includes demographics, family history of cleft, diet and water sources, maternal pregnancy history, and other lifestyle and environmental factors. Results: Seven of 8 countries are currently summarized (2012-2017) for a total of 2955 case and 2774 control families with 11 946 unique biological samples from Vietnam, Philippines, Honduras, Madagascar, Morocco, Democratic Republic of the Congo, and Nicaragua. The phenotype distribution was 1641 (55.5%) cases with cleft lip and palate, 782 (26.5%) with cleft lip (CL), and 432 (14.6%) with cleft palate (CP). Discussion: The International Family Study is the largest case set of NSOFCs with an associated biobank in LMICs currently assembled. The biobank, family, and case–control study now include samples from 8 LMICs where local health care infrastructure cannot address the surgical burden of cleft or investigate causal mechanisms. The International Family Study can be a source of information and may collaborate with local public health institutions regarding education and interventions to potentially prevent NSOFCs.